Validation of a Simple Score for Mortality Prediction in a Cohort of Unselected Emergency Patients - Jeannette-Marie Busch; Isabelle Arnold; John Kellett; Mikkel Brabrand; Roland Bingisser; Christian H. Nickel (International Journal of Clinical Practice)
Background. Prognostication is an important component of medical decision-making. A patients’ general prognosis can be difficult to measure. The Simple Prognostic Score (SPS) was designed to include patients’ age, mobility, aggregated vital signs, and the treating physician’s decision to admit to aid prognostication. Study Aim. Our study aim is to validate the SPS, compare it with the Emergency Severity Index (ESI) regarding its prognostic performance, and test the interrater reliability of the subjective variable of the decision to admit. Methods. Over a period of 9 weeks all patients presenting to the ED were included, routinely interviewed, final disposition registered, and followed up for one year. The C-statistics of discrimination was used to compare SPS and ESI predictions of 7-day, 30-day, and 1-year mortality. Youden J Statistics and Odds ratio, using logistical regression, were calculated for the Simple Prognostic Score. In a subset, a chart review was performed by senior physicians for a secondary assessment of the decision to admit. Interrater reliability was calculated using percentages and Cohens Kappa. Results. Out of 5648 patients, 3272 (57.9%) had a low SPS (i.e., ≤ 1); none of these patients died within 7 days, 2 (0.1%) died within 30 days after presentation and 19 (0.6%) died within a year. The area under the curve for 1-year mortality of the Simple Prognostic Score was 0.848. Secondary analysis of the interrater agreement for the decision to admit was 92%. Conclusion. In a prospective study of unselected ED patients, the Simple Prognostic Score was validated as a reliable predictor of short- and long-term mortality.